Pengembangan Bahan Ajar PAI Berbasis Nilai Nilai Kearifan Lokal di SMP - sahid; Angga dwi saputra p k; Elih Herliana; Fiqra Muhamad Nazib (Yayasan Al-Afif, 2024)
Development of Islamic Religious Education (PAI) teaching materials based on local wisdom values in Junior High Schools (SMP) aims to unite Islamic teachings with local culture, making religious education more relevant and meaningful for students. Amid globalization, the integration of local cultural values into PAI teaching materials is expected to enrich students' learning experiences by presenting religious teachings in the context of daily life. This research uses the Systematic Literature Review (SLR) method to explore strategies, implementation, and evaluation of locally-based teaching materials. The research findings indicate that the strategies applied include the integration of local cultural values, the use of traditional stories, and methods that are appropriate to the students' environment. The implementation of these teaching materials not only strengthens religious understanding but also preserves local wisdom. Evaluation shows the need to adjust the curriculum to the cultural context and the needs of the students.